Cross-cultural adaptation and validation of The Resilience Scale for Kidney Transplantation (RS-KTPL) in a Chinese population. - Yan Tang; Jiefu Zhu; Tao Qiu; Shan Qiu; Wei Lei; Xiaolan Mao (PLoS ONE)
Objective This study aimed to translate and validate The Resilience Scale for Kidney Transplantation (RS-KTPL) into Chinese and assess its reliability and validity among kidney transplant patients in China. Methods With authorization from the original authors, the RS-KTPL was translated following Brislin's translation model, including forward translation, back translation, author review, cross-cultural adaptation, and a pilot study, resulting in a Chinese version of the RS-KTPL. A total of 358 kidney transplant recipients were recruited through convenience sampling and completed the questionnaire. Statistical analyses included item analysis, content validity, structural validity, convergent validity, discriminant validity, and reliability. Results Item analysis led to the removal of certain items that did not meet the criteria, resulting in a final version of the scale with 22 items across four dimensions. For content validity, the item-level content validity index (I-CVI) ranged from 0.83 to 1.000, and the scale-level content validity index (S-CVI/Ave) was 0.91, indicating good content fit. Structural validity was confirmed through exploratory and confirmatory factor analyses, supporting a four-factor structure with a cumulative variance contribution rate of 64.913% and all factor loadings exceeding 0.5. Convergent and discriminant validity analyses showed that the composite reliability (CR) values ranged from 0.741 to 0.938, and the average variance extracted (AVE) values ranged from 0.5 to 0.704, with the square root of AVE being higher than the inter-factor correlation coefficients, indicating good internal consistency and discriminating ability. Reliability testing showed a Cronbach's α coefficient of 0.944 for the overall scale, with subscale Cronbach's α coefficients all above 0.696, and a split-half reliability of 0.891, demonstrating high internal consistency and stability of the scale. Conclusion The Chinese version of the RS-KTPL exhibits good reliability and validity among kidney transplant patients in China and can be effectively used to assess psychological resilience in this population.